CLOUD COMPUTING: TRANSFORMING THE HEALTH INSURANCE LANDSCAPE - Venkata Bhanuprasad Ananthavaram, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
Cloud computing has emerged as a transformative force in the health insurance industry, revolutionizing traditional operational models and service delivery mechanisms. The integration of cloud technologies has fundamentally altered claims processing, data analytics, interoperability, and security frameworks across the healthcare sector. From streamlining revenue cycle management to enabling AI-powered insights and facilitating telehealth services, cloud platforms have enhanced operational efficiency while reducing costs. The implementation of advanced security protocols and compliance measures has strengthened data protection while maintaining accessibility. Despite challenges in integration and data sovereignty, the adoption of cloud computing continues to drive innovation in personalized insurance products and value-based care models, marking a significant shift in healthcare delivery and management